Studi Sekuensial Eksplanatori: Aktivitas Fisik dan Kebugaran Fisik Masa Pandemi Guru Pendidikan Jasmani Olahraga dan Kesehatan - Abisibah Abisibah; Sakban Rosidi; Adi Sucipto (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
This study has the goal to assess physical activity, physical fitness based on the specified category criteria, and to know the physical activity relationship with physical fitness and understanding perception, advice of the teacher's hopes during the Pandemic of Covid-19. This study used a combined method (mixed method) is a blend of quantitative and qualitative research with sequential explanatory approach.The combined research method (mixed method) is the initial order of using quantitative data then clarified with the results of qualitative data, as follows: (a) the first hypothesis is known to physical activity in the teacher with a 17.00 lower than the criteria either 20.4. This means that there is a significant difference between the average by good criteria, in which the correct state is below good category criteria. (b) The second hypothesis is known to be physical fitness teachers including good categories, is 47,2045 which is higher than the criteria either, 40.8. In this case the average has a good category criteria. (c) The third hypothesis significant relationships at the level of physical activity and physical fitness level of the teachers is the correlation coefficient of 0.370, so if the physical activity is high, the physical fitness is higher as well. Kata Kunci: Studi Sukensial Eksplanatori; Aktivitas Fisik; Kebugaran Fisik